Odpowiedzi

2009-11-28T17:25:38+01:00
A) 3x=12
x - y = 1

x=4
4-y=1

x=4
y=3

c) x-2y
-2x + y = 0

tu jest jakiś błąd chyba w pierwszym.


d) 2x + y = 9
5x - 4y = 3

y=9-2x
5x-4y=3

y=9-2x
5x-4(9-2x)=3

y=9-2x
5x-36+8x=3

y=9-2x
13x=39

y=9-6
x=3

y=3
x=3
2009-11-28T17:28:08+01:00
A) 3x=12 |:3
x - y = 1

x=4
4-y = 1
-y = 1 - 4
-y = -3|*(-1)
y = 3


c) x-2y = 0
-2x + y = 0

x = 2y

-2*2y + y = 0
-4y + y = 0
-3y = 0|:(-3)
y = 0
x = 2*0
x=0

d) 2x + y = 9
5x - 4y = 3

y = 9 - 2x
5x - 4(9 - 2x) = 3
5x -36 + 8x = 3
5x + 8x = 3+36
13x = 39 |:13
x = 3

5x - 4y = 3
5*3 - 4y = 3
15-3 = 4y |:4
y = 3
2009-11-28T20:03:04+01:00
3x=12
x- y=1
x=4
4-y=1
x=4
-y=1-4(.-1)
y=3

d)2x+y=9
5x-4y=3
y=9-2x
5x-4(9-2x)=3
y=9-2x
5x-36+8x=3
y=9-2x
c) chyba zle wpisane
13x=39
x=3
y=9-2(3)
y=3